Tumours and tumour like lesions of larynx: a clinicopathological study - Kavitha, Y.; Chaitanya, V.; Basavaraju, K. P. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Larynx is an important structure in human being forming a part of upper airway and responsible for voice production. Varieties of tumours and tumour like lesions of larynx significantly affect its functions. The aim of the study was to study the clinicopathological aspects of various lesions of larynx. Methods: An observational study was conducted from January 2012 to December 2017 in a tertiary care centre retrospectively. Data collected from departmental registers. History, clinical presentation, relevant investigations and histopathology of biopsy from laryngeal lesions were analysed. Results: The incidence of laryngeal lesions was found to be high between 30-40 years (30.8%) followed by 51-60 years age group (20.9%) with higher preponderance among males (80.25%) compared to females (19.75%). Hoarseness of voice was the commonest presenting symptom in our patients accounting for 80%. It was observed that 27.1% patients were smokers, 10% were addicted to alcohol, and 6% patients had history of both smoking and alcohol consumption. Vocal polyp was the commonest tumour like lesion found in our study (31.4%) followed by vocal nodule (14.1%). Laryngeal papilloma was the only type of benign tumour found in our study (8%) and squamous cell carcinoma of larynx accounts for majority of malignant tumours most of which were moderately differentiated (40%). Conclusions: Majority of the laryngeal lesions are seen among rural population with poor socioeconomic status. Hence, creating awareness about risk factors, symptomatology and better cure with early detection can be life saving.